CDK1 switches mitotic arrest to apoptosis by phosphorylating Bcl‐2/Bax family proteins during treatment with microtubule interfering agents. (18th March 2014) - Zhou, Lingli; Cai, Xiaoling; Han, Xueyao; Xu, Naihan; Chang, Donald C.
Abstract Microtubule interfering agents (MIAs), that can stabilise or depolymerise microtubules, are an important class of cancer chemotherapeutic drugs. They can lead to mitotic arrest and subsequent apoptosis. We demonstrate that cell cycle‐dependent kinase 1 (CDK1) is important in switching cells from mitotic arrest to apoptosis during MIAs treatment. Overexpression of non‐degradable cyclin B1 sustained CDK1 activation and mitotic arrest, followed by caspase‐3 dependent apoptosis. CDK1 is responsible for the phosphorylation of several pro‐ and anti‐apoptotic Bcl‐2 family proteins during MIAs treatment. CDK1‐mediated Bcl‐2 serine 70 phosphorylation enhances its pro‐apoptotic function, whereas CDK1‐mediated Bad serine 128 phosphorylation promotes apoptosis. Blockage of CDK1 activity with a specific pharmacological inhibitor suppresses Mcl‐1 phosphorylation, degradation and its anti‐apoptotic function. Therefore, the death of cancer cells under MIAs treatment was caused by imbalance between CDK1‐induced alterations in the pro‐apoptotic and anti‐apoptotic functions of phosphorylated Bcl‐2 family proteins.